Calculating Disability-Adjusted Life Years (DALY) for traffic accidents and its economic consequences in Ecuador - Mauricio Cuesta Zapata (Revista Latinoamericana de Población)
Road traffic fatalities in Ecuador are 20.4 deaths per 100,000 people. Men are the most affected by traffic accidents: 4.2 times higher than women (33 vs. 7.8 deaths per 100,000 people, respectively). Traffic accidents show a decrease: from 22 deaths per 100,000 people in 2010 to 18 deaths per 100,000 people in 2016. The estimation of DALY by the life expectancy method used age weighting β = 0.04, r = 0.03, C = 0.1658. The average burden of disease is 141,430 DALY or 897 DALY per 100,000 people (95% CI 892-902). The cost of DALY, using the approach of human capital, is US$ 806.8 million equivalent to 0.89% of GDP, 81% caused by males and 19% by females. This percentage of GDP lost for road fatalities is equivalent as if each individual in Ecuador paid US$ 358 annually. The provinces with the largest population (Guayas, Pichincha, & Manabí) contribute with the 52% to the total population, 67% to the number of vehicles and 49% of total deaths due to traffic accidents. However, when we analyze deaths per number of people and number of vehicles, these provinces are not the most dangerous for dying in a traffic accident. Considering number of deaths per 100,000 people, the most dangerous provinces are Sucumbíos (33.5), Cotopaxi (32.0), Orellana (31.2), together, they constitute just the 5.9% of the population and 3.8% of the total vehicles, however, the average death rate of these three provinces is 1.58 times the national average (20.4 per 100,000 people). Considering the number of deaths per 100,000 vehicles, the most dangerous provinces are Napo (460), Imbabura (429) and Morona Santiago (400), together, they constitute just the 4.5% of the population and 1.9% of the total vehicles, however, the average death rate of these three provinces is 2.7 times the national average (156 per 100,000 vehicles).